A silicone rubber composite material for fire-resistant cable and preparation method thereof

By blending vinyl silicone oil, neoprene and modified inorganic particles with hyperbranched polysiloxane and vulcanized, a silicone rubber composite material for refractory cables was prepared, which solved the flammable silicone rubber material at high temperatures. The problem has significantly improved its fracture strength and refractory performance, meeting the high safety performance requirements of modern industry for refractory materials.

CN114516980BActive Publication Date: 2025-01-14鹰潭市康大塑胶有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210215832.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-07
Publication Date
2025-01-14
Estimated Expiration
2042-03-07

AI Technical Summary

Technical Problem

The existing silicone rubber materials are flammable at high temperatures, and the ceramic layer structure generated after combustion is difficult to meet the needs of modern industry in terms of fire resistance, especially in the fields of wires, cables and electronic equipment.

Method used

Vinyl silicone oil, neoprene and modified inorganic particles are blended with hyperbranched polysiloxane, and silicone rubber composite materials for refractory cables are prepared by first- and second-stage vulcanization treatment to form low-melting point inorganic particles and branched long chains Structure to improve fracture strength and fire resistance.

Benefits of technology

The breaking strength and refractory performance of silicone rubber composite materials for refractory cables is significantly improved, forming a solid ceramic layer structure to prevent flame spread and isolate heat, and meet the high safety performance requirements of modern industry for refractory materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a silicone rubber composite material for fire-resistant cables and a preparation method thereof, and relates to the technical field of rubber materials. When preparing the silicone rubber composite material for fire-resistant cables, the invention calcines sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide, performs multi-stage cooling treatment to obtain low-melting-point inorganic particles, hydrolyzes ethyl orthosilicate and deposits it on the surface of the low-melting-point inorganic particles, then reacts methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane and grafts the surface to obtain modified inorganic particles, reacts methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane to obtain hyperbranched polysiloxane, and vinyl silicone oil, chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane are blended, and the silicone rubber composite material for fire-resistant cables is obtained after one-stage vulcanization and two-stage vulcanization. The silicone rubber composite material for fire-resistant cables prepared by the invention has excellent fracture resistance and fire resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber materials, in particular to a silicone rubber composite material for fire-resistant cables and a preparation method thereof. Background Art

[0002] At present, with the rapid development of the power industry, the use of wires and cables has increased sharply. In 2010, the total output value of the industry reached more than 930 billion yuan, and the number of employees exceeded 720,000. In terms of scale, my country has become the world's largest producer of wires and cables. The rapid development and transformation and upgrading of the industry have brought about a desire for the improvement of technical levels and the development of high-safety wires and cables. In particular, the research and utilization of new wire and cable materials are of great significance to the development of the wire and cable industry. Since most of the wires and cables widely used in various departments such as industry, agriculture and military are old-fashioned PVC wires and cables, and a large amount of flammable materials such as plasticizers are added to PVC materials, many PVC cables have a high heat release rate and high calorific value when burning, and produce a large amount of thick smoke and toxic gases, which not only harms the environment but also poses a serious threat to the safety of personnel. In recent years, social fire awareness has gradually increased, and the rapid development of wire and cable materials in the field of fire protection has become an urgent need.

[0003] Although the structure of silicone rubber is very stable, it is still a flammable substance. It will continue to burn when it encounters high temperature or open flame, and it will continue to smolder even after the open flame is extinguished. Therefore, this has affected the application of silicone rubber in wire and cable, electronic appliances, automobile industry and aviation to a certain extent. However, after the silicone rubber burns, a hard and brittle white shell of silicon-carbon structure will be formed on the surface, and this shell can isolate the flame and prevent heat propagation. Therefore, the burning rate of silicone rubber is very low, and there are many residues after burning. Refractory silicone rubber is based on this. By adding porcelain-forming materials, the residues of the silicone rubber substrate and the porcelain-forming materials are bonded together at a high temperature of more than 500°C, and burned to form a solid ceramic layer structure. This solid ceramic layer structure can prevent the open flame from spreading inward, isolate most of the heat from the outside of the ceramic layer, and the longer the burning time at high temperature, the stronger the ceramic body. Due to the needs of fire prevention at home and abroad, silicone rubber that has not been flame-retardant or fire-resistant can no longer meet the requirements of modern industry. With the enhancement of fire awareness, it is necessary to develop refractory silicone rubber with better fire resistance. Summary of the invention

[0004] The object of the present invention is to provide a silicone rubber composite material for fire-resistant cables and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a silicone rubber composite material for a fire-resistant cable, characterized in that the silicone rubber composite material for a fire-resistant cable is prepared by blending vinyl silicone oil, chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane, and performing one-stage vulcanization and two-stage vulcanization under the action of a vulcanizing agent.

[0007] As an optimization, the modified inorganic particles are prepared by calcining sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide, subjecting them to multi-stage cooling treatment and then grinding them into low-melting-point inorganic particles, hydrolyzing ethyl orthosilicate and depositing it on the surface of the low-melting-point inorganic particles, and treating them with sodium hydroxide to obtain pre-modified inorganic particles, and then reacting methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane and grafting them onto the pre-modified inorganic particles to obtain the obtained particle.

[0008] As an optimization, the hyperbranched polysiloxane is prepared by reacting methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane.

[0009] As an optimization, the preparation method of the silicone rubber composite material for fire-resistant cables includes the following preparation steps:

[0010] (1) mixing sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide in a mass ratio of 1:1:4:16:16 to 1:1:6:22:20, calcining at 1000 to 1200° C. for 50 to 60 minutes, performing a multi-stage cooling treatment, and then grinding in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles;

[0011] (2) in a nitrogen atmosphere, methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol are mixed uniformly in a mass ratio of 1:3:2:8 to 1:4:2:10, and then the pH is adjusted to 2.9 to 3.1 with 3 to 5% hydrochloric acid, and stirred at 30 to 40° C. and 500 to 800 r / min for 40 to 50 min, and then 1 to 2 times the mass of methyltrimethoxysilane pre-modified inorganic particles are added, and the reaction is stirred at 70 to 78° C. and 500 to 800 r / min for 12 to 18 h, filtered and washed with anhydrous ethanol for 3 to 5 times, and dried at 60 to 70° C. for 4 to 6 h to obtain modified inorganic particles;

[0012] (3) Vinyl silicone oil, chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane are mixed uniformly in a mass ratio of 10:20:8:5 to 15:30:12:8, and a vulcanizing agent of 0.05 to 0.08 times the mass of the vinyl silicone oil is added, and the mixture is stirred at 60 to 70°C and 800 to 1000 r / min for 20 to 30 min, and allowed to stand at room temperature for 20 to 24 h, and then placed in a mold for one-stage vulcanization, and then subjected to two-stage vulcanization in a vacuum drying oven to obtain a silicone rubber composite material for fire-resistant cables.

[0013] As an optimization, the multi-stage cooling treatment method in step (1) is: cooling at 400-500°C for 2-3h, cooling at 100-150°C for 1-2h, and cooling at 10-30°C for 50-60min.

[0014] As an optimization, the preparation method of the pre-modified inorganic particles in step (2) is: low-melting point inorganic particles and 25-30% by mass of ammonia water, anhydrous ethanol and pure water are mixed uniformly in a ratio of 1:2:4:2-1:3:5:2, and then 1-1.2 times the mass of low-melting point inorganic particles of tetraethyl orthosilicate are added, and the mixture is stirred at 20-30°C and 500-800r / min for 2-3h and then filtered, and then washed with deionized water and anhydrous ethanol for 3-5 times each, and then immersed in a sodium hydroxide solution with a mass fraction of 5-8%, and then ultrasonically reacted at 50-60°C and 30-40kHz for 22-24h, and then filtered, and then washed with pure water and anhydrous ethanol for 3-5 times each, and then dried at -10--1°C and 5-10Pa for 6-8h to prepare.

[0015] As an optimization, the preparation method of the hyperbranched polysiloxane in step (3) is as follows: methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol are uniformly mixed in a mass ratio of 1:3:2:8 to 1:4:2:10 in a nitrogen atmosphere, and then the pH is adjusted to 2.9 to 3.1 with 3 to 5% hydrochloric acid by mass, and stirred at 30 to 40° C. and 500 to 800 r / min for 40 to 50 min, and then 1.4 to 1.6 times the mass of vinyltrimethoxysilane is added. The organic silicon mixed solution is stirred and reacted at 50-60°C and 500-800r / min for 2-3h, then the temperature is raised to 70-78°C and the stirring reaction is continued for 7-9h, then an aqueous hexamethyldisiloxane solution with a mass fraction of 85-90% and a mass fraction of 1.9-2.1 times the mass of vinyltrimethoxysilane is added and the stirring reaction is continued for 5-7h, and the solution is allowed to stand at 10-30°C for 8-10h, and the lower layer of oily substance is separated by a separatory funnel, and dried at 10-30°C and 1-10Pa for 8-10h to prepare the product.

[0016] As an optimization, the organic silicon mixed solution is prepared by uniformly mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:3:2 to 1:4:3.

[0017] As an optimization, the model of the mercapto silicone oil in step (3) is DMS-V21; the chloroprene rubber is W-type chloroprene rubber; and the vulcanizing agent is dipentadienyl vulcanizing agent.

[0018] As an optimization, the process conditions of the first-stage vulcanization in step (3) are: vulcanization temperature 160-170°C, vulcanization pressure 480-500MPa, and vulcanization time 20-30min; the process conditions of the second-stage vulcanization are: vulcanization temperature 170-180°C, vulcanization pressure 300-500Pa, and vulcanization time 2-3h.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] When preparing the silicone rubber composite material for fire-resistant cables, the present invention mixes vinyl silicone oil, chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane, and performs one-stage and two-stage vulcanization under the action of a vulcanizing agent to obtain the silicone rubber composite material for fire-resistant cables.

[0021] First, sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are calcined, subjected to multi-stage cooling treatment, and then ground into low-melting-point inorganic particles. When potassium carbonate and sodium carbonate are calcined, gas, potassium oxide and sodium oxide can be generated, and the calcined and molten inorganic components can be stirred to mix evenly. At the same time, the generated potassium oxide and sodium oxide can provide free oxygen, and the free oxygen can combine with bismuth to form more bismuth oxygen tetrahedron and bismuth oxygen octahedron structures, resulting in a decrease in the integrity of the inorganic network formed by boron, silicon and oxygen elements, making the obtained low-melting-point inorganic particles easier to melt, and can respond to high temperature in time and form a molten state to cover the surface of the cable for fire protection and heat insulation, while absorbing free radicals generated by heat, thereby improving the fire resistance. Multi-stage cooling treatment can avoid the low-melting-point inorganic particles obtained by rapid cooling of the glass melt at room temperature. The components are mixed unevenly, thereby further improving the fire resistance; the low-melting point inorganic particles are modified to form a porous silica layer on the surface and branched long chains formed by organic silicon reaction are grafted onto the porous silica layer. The vinyl contained on the branched long chains can participate in the subsequent vulcanization, so that the modified inorganic particles play a role in cross-linking and strengthening the main body of the silicone rubber composite material for fire-resistant cables, thereby improving the fracture strength of the silicone rubber composite material for fire-resistant cables. The porous silica layer can protect the low-melting point inorganic particles inside. At high temperatures, molten inorganic matter is formed inside the modified inorganic particles, and the branched long chains are broken and cross-linked to form free radicals on the outside of the modified inorganic particles. They have good compatibility with molten inorganic matter and guide the outflow and expansion of the molten inorganic matter, thereby improving the fire resistance of the silicone rubber composite material for fire-resistant cables.

[0022] Secondly, a hyperbranched polysiloxane prepared by the reaction of methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane is added. The hyperbranched structure can improve the cross-linking effect, and the branch gap is easy to fix other components, thereby improving the fracture strength. When melted, the hyperbranched polysiloxane has good fluidity and compatibility with inorganic substances, avoiding the dripping of molten inorganic substances, and adhering to the cable conductor to avoid bare leakage of the conductor, thereby improving the fire resistance; a two-stage vulcanization treatment is carried out to volatilize the volatile small molecules and small molecule free radicals in the components in a vacuum environment, avoiding the small molecules and small molecule free radicals from causing a decrease in the degree of cross-linking, thereby improving the fracture strength of the silicone rubber composite material for fire-resistant cables. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the fire-resistant cable silicone rubber composite material prepared in the following examples are as follows:

[0025] Fracture resistance: The fire-resistant silicone rubber composite material for cables obtained in each embodiment and the comparative example material were taken into the same size and shape, and the tensile strength at the time of tensile fracture was tested according to GB / T1701.

[0026] Fire resistance: The fire-resistant silicone rubber composite material for cables obtained in each embodiment and the comparative material were applied to the same cable as a sheath of the same thickness, and the cables of the same length were taken to test the limiting oxygen index according to GB / T2046.

[0027] Example 1

[0028] A method for preparing a silicone rubber composite material for a fire-resistant cable, the method for preparing a silicone rubber composite material for a fire-resistant cable mainly comprising the following preparation steps:

[0029] (1) Sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are uniformly mixed in a mass ratio of 1:1:4:16:16, calcined at 1000°C for 60 minutes, and then subjected to a multi-stage cooling treatment, cooling at 400°C for 3 hours, cooling at 100°C for 2 hours, and cooling at 10°C for 60 minutes, and then ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles;

[0030] (2) low-melting-point inorganic particles and 30% by mass of ammonia water, anhydrous ethanol and pure water were mixed in a ratio of 1:2:4:2, and then 1 times the mass of low-melting-point inorganic particles of tetraethyl orthosilicate was added, stirred at 20°C and 500 r / min for 3 hours, filtered, washed with deionized water and anhydrous ethanol three times each, immersed in a 5% by mass sodium hydroxide solution, ultrasonically reacted at 50°C and 30kHz for 24 hours, filtered, washed with pure water and anhydrous ethanol three times each, and dried at -10°C and 5Pa for 8 hours to obtain a prepreg. Modifying inorganic particles: methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol are uniformly mixed in a mass ratio of 1:3:2:8 in a nitrogen atmosphere, and then the pH is adjusted to 2.9 with 3% hydrochloric acid, and stirred at 30°C and 500r / min for 50min, and then pre-modified inorganic particles with a mass of 1 times that of methyltrimethoxysilane are added, and the mixture is stirred at 70°C and 500r / min for 18h, filtered and washed with anhydrous ethanol for 3 times, and dried at 60°C for 6h to obtain modified inorganic particles;

[0031] (3) Methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed in a mass ratio of 1:3:2:8 in a nitrogen atmosphere, and the pH was adjusted to 2.9 with 3% hydrochloric acid, and stirred at 30°C and 500 r / min for 40 min. Then, an organic silicon mixed solution prepared by mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:3:2 with 1.4 times the mass of vinyltrimethoxysilane was added, and stirred at 50°C and 500 r / min for 3 h. The temperature was then raised to 70°C and the stirring was continued for 9 h. Then, 85% hexamethyldisilazane with a mass fraction of 1.9 times the mass of vinyltrimethoxysilane was added. The oxane aqueous solution was stirred and reacted for 7 hours, and the mixture was allowed to stand at 10°C for 10 hours. The lower layer of oil was separated by a separatory funnel and dried at 10°C and 1Pa for 10 hours to obtain hyperbranched polysiloxane; vinyl silicone oil, W-type chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane were evenly mixed in a mass ratio of 10:20:8:5, and a dipentadienyl vulcanizing agent with a mass of 0.05 times that of the vinyl silicone oil was added, and the mixture was stirred at 60°C and 800r / min for 30 minutes, and allowed to stand at room temperature for 24 hours, and then placed in a mold for one-stage vulcanization, and vulcanized at 160°C and 480MPa for 30 minutes, and then vulcanized in a vacuum drying oven for two stages, and vulcanized at 170°C and 300Pa for 3 hours to obtain a silicone rubber composite material for fire-resistant cables.

[0032] Example 2

[0033] A method for preparing a silicone rubber composite material for a fire-resistant cable, the method for preparing a silicone rubber composite material for a fire-resistant cable mainly comprising the following preparation steps:

[0034] (1) Sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are uniformly mixed in a mass ratio of 1:1:5:19:18, calcined at 1100° C. for 55 minutes, and then subjected to a multi-stage cooling treatment, cooling at 450° C. for 2.5 hours, cooling at 120° C. for 1.5 hours, and cooling at 20° C. for 55 minutes, and then ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles;

[0035] (2) low-melting-point inorganic particles and 28% by mass of ammonia water, anhydrous ethanol and pure water were mixed uniformly in a ratio of 1:2.5:4.5:2, and then 1.1 times the mass of low-melting-point inorganic particles of tetraethyl orthosilicate was added, stirred at 25°C and 650r / min for 2.5 hours, filtered, washed with deionized water and anhydrous ethanol four times respectively, immersed in a 6% by mass sodium hydroxide solution, ultrasonically reacted at 55°C and 35kHz for 23 hours, filtered, washed with pure water and anhydrous ethanol four times respectively, dried at -5°C and 8Pa for 7 hours, and prepared To obtain pre-modified inorganic particles, methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed uniformly in a mass ratio of 1:3.5:2:9 in a nitrogen atmosphere, and the pH was adjusted to 3 with 4% hydrochloric acid, and stirred at 35°C and 650r / min for 45min, and then 1.5 times the mass of methyltrimethoxysilane pre-modified inorganic particles were added, and the mixture was stirred at 74°C and 650r / min for 16h, filtered and washed with anhydrous ethanol for 4 times, and dried at 65°C for 5h to obtain modified inorganic particles;

[0036] (3) Methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed in a mass ratio of 1:3.5:2:9 in a nitrogen atmosphere, and the pH was adjusted to 3 with 4% hydrochloric acid, and stirred at 35°C and 600 r / min for 45 min. Then, an organic silicon mixed solution prepared by mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:3.5:2.5 with a mass ratio of 1.5 times that of vinyltrimethoxysilane was added, and the mixture was stirred at 55°C and 650 r / min for 2.5 h. The mixture was heated to 74°C and stirred for 8 h. Then, 88% hexamethyldisilazane with a mass ratio of 2 times that of vinyltrimethoxysilane was added. The oxane aqueous solution was stirred and reacted for 6 hours, and then allowed to stand at 20°C for 9 hours. The lower layer of oil was separated by a separatory funnel and dried at 20°C and 5Pa for 9 hours to obtain hyperbranched polysiloxane; vinyl silicone oil, W-type chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane were evenly mixed in a mass ratio of 12:25:10:6.5, and a dipentadienyl vulcanizing agent with a mass of 0.06 times that of the vinyl silicone oil was added, and stirred at 65°C and 900r / min for 25 minutes, and allowed to stand at room temperature for 22 hours, and then placed in a mold for one-stage vulcanization, and vulcanized at 165°C and 490MPa for 25 minutes, and then vulcanized in a vacuum drying oven for two stages, and vulcanized at 175°C and 400Pa for 2.5 hours to obtain a silicone rubber composite material for fire-resistant cables.

[0037] Example 3

[0038] A method for preparing a silicone rubber composite material for a fire-resistant cable, the method for preparing a silicone rubber composite material for a fire-resistant cable mainly comprising the following preparation steps:

[0039] (1) Sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are uniformly mixed in a mass ratio of 11:1:6:22:20, calcined at 1200° C. for 50 min, and then subjected to a multi-stage cooling treatment, cooling at 500° C. for 2 h, cooling at 150° C. for 1 h, and cooling at 10° C. for 50 min, and then ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles;

[0040] (2) low-melting-point inorganic particles and 25% by mass of ammonia water, anhydrous ethanol and pure water were mixed uniformly in a ratio of 1:3:5:2, and then 1.2 times the mass of low-melting-point inorganic particles of tetraethyl orthosilicate was added, stirred at 30°C and 800 r / min for 3 hours, filtered, washed with deionized water and anhydrous ethanol 5 times each, immersed in 8% by mass sodium hydroxide solution, ultrasonically reacted at 60°C and 40kHz for 22 hours, filtered, washed with pure water and anhydrous ethanol 5 times each, and dried at -1°C and 10Pa for 8 hours to obtain a prepreg. Modifying inorganic particles: methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol are uniformly mixed in a mass ratio of 1:4:2:10 in a nitrogen atmosphere, and then the pH is adjusted to 3.1 with 5% hydrochloric acid, and stirred at 40°C and 800 r / min for 40 minutes, and then pre-modified inorganic particles twice the mass of methyltrimethoxysilane are added, and the reaction is stirred at 78°C and 800 r / min for 18 hours, filtered and washed with anhydrous ethanol for 5 times, and dried at 70°C for 4 hours to obtain modified inorganic particles;

[0041] (3) Methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed in a mass ratio of 1:4:2:10 in a nitrogen atmosphere, and the pH was adjusted to 3.1 with 5% hydrochloric acid, and stirred at 40°C and 800 r / min for 40 min. Then, an organic silicon mixed solution prepared by mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:4:3 with 1.6 times the mass of vinyltrimethoxysilane was added, and stirred at 60°C and 800 r / min for 2 h. The temperature was then raised to 78°C and the stirring reaction was continued for 7 h. Then, 85% hexamethyldisilazane with a mass fraction of 2.1 times the mass of vinyltrimethoxysilane was added. The oxane aqueous solution was stirred and reacted for 5 hours, and then allowed to stand at 30°C for 8 hours. The lower layer of oil was separated by a separatory funnel and dried at 30°C and 10Pa for 8 hours to obtain hyperbranched polysiloxane; vinyl silicone oil, W-type chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane were evenly mixed in a mass ratio of 15:30:12:8, and a dipentadienyl vulcanizing agent with a mass of 0.08 times that of the vinyl silicone oil was added, and the mixture was stirred at 70°C and 1000r / min for 30 minutes, and allowed to stand at room temperature for 20 hours, and then placed in a mold for one-stage vulcanization, and vulcanized at 170°C and 500MPa for 30 minutes, and then vulcanized in a vacuum drying oven for two stages, and vulcanized at 180°C and 500Pa for 2 hours to obtain a silicone rubber composite material for fire-resistant cables.

[0042] Comparative Example 1

[0043] The preparation method of the fire-resistant cable silicone rubber composite material of Comparative Example 1 is different from that of Example 2 only in step (1), and step (1) is modified as follows: Boric acid, silicon dioxide and bismuth trioxide are mixed uniformly in a mass ratio of 5:19:18, calcined at 1100°C for 55 minutes, and then subjected to multi-stage cooling treatment, cooling at 450°C for 2.5 hours, cooling at 120°C for 1.5 hours, and cooling at 20°C for 55 minutes, and then ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles. The remaining steps are the same as in Example 2.

[0044] Comparative Example 2

[0045] The preparation method of the fire-resistant cable silicone rubber composite material of Comparative Example 2 is different from that of Example 2 only in step (1), and step (1) is modified as follows: sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are mixed uniformly in a mass ratio of 1:1:5:19:18, calcined at 1100°C for 55 minutes, cooled at 20°C for 55 minutes, and ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles. The remaining steps are the same as in Example 2.

[0046] Comparative Example 3

[0047] The preparation method of the fire-resistant cable silicone rubber composite material of Comparative Example 3 is different from that of Example 2 only in step (2), and step (2) is modified as follows: low-melting inorganic particles and 25% by mass of ammonia water, anhydrous ethanol and pure water are mixed uniformly in a ratio of 1:3:5:2, and then 1.2 times the mass of low-melting inorganic particles of tetraethyl orthosilicate is added, and the mixture is stirred at 30°C and 800r / min for 3h and filtered, and then washed with deionized water and anhydrous ethanol 5 times each, and then immersed in a sodium hydroxide solution with a mass fraction of 8%, and then filtered after ultrasonic reaction at 60°C and 40kHz for 22h, and then washed with pure water and anhydrous ethanol 5 times each, and then dried at -1°C and 10Pa for 8h to obtain modified inorganic particles. The remaining steps are the same as Example 2.

[0048] Comparative Example 4

[0049] The preparation method of the fire-resistant cable silicone rubber composite material of Comparative Example 4 is different from that of Example 2 only in step (2), and step (2) is modified as follows: methyl trimethoxysilane, diphenyl dimethoxysilane, vinyl trimethoxysilane and ethanol are mixed uniformly in a mass ratio of 1:3.5:2:9 in a nitrogen atmosphere, and then the pH is adjusted to 3 with 4% hydrochloric acid, and stirred at 35°C, 650r / min for 45min, and then low-melting-point inorganic particles with a mass of 1.5 times that of methyl trimethoxysilane are added, and the reaction is stirred at 74°C, 650r / min for 16h, filtered and washed with anhydrous ethanol 4 times, and dried at 65°C for 5h to obtain modified inorganic particles. The remaining steps are the same as those of Example 2.

[0050] Comparative Example 5

[0051] The preparation method of the fire-resistant cable silicone rubber composite material of comparative example 5 is different from that of example 2 only in step (23), and step (3) is modified as follows: vinyl silicone oil, W-type chloroprene rubber and modified inorganic particles are mixed uniformly in a mass ratio of 12:25:10, a dipentadienyl vulcanizing agent of 0.06 times the mass of the vinyl silicone oil is added, stirred at 65°C and 900r / min for 25min, and allowed to stand at room temperature for 22h, then placed in a mold for one-stage vulcanization, vulcanized at 165°C and 490MPa for 25min, and then vulcanized in a vacuum drying oven for two stages, and vulcanized at 175°C and 400Pa for 2.5h to obtain a fire-resistant cable silicone rubber composite material. The remaining steps are the same as in example 2.

[0052] Comparative Example 6

[0053] The preparation method of the silicone rubber composite material for fire-resistant cables of Comparative Example 6 is different from that of Example 2 only in step (3). Step (3) is modified as follows: methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol are mixed uniformly in a mass ratio of 1:3.5:2:9 in a nitrogen atmosphere, and the pH is adjusted to 3 with 4% hydrochloric acid, and stirred at 35°C and 600r / min for 45min, and then a mixed organic silicon solution prepared by mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:3.5:2.5 with a mass ratio of 1.5 times that of vinyltrimethoxysilane is added, and the reaction is stirred at 55°C and 650r / min for 2.5h, and then The temperature was raised to 74°C and the mixture was stirred and reacted for 8 hours. Then, an aqueous hexamethyldisiloxane solution with a mass fraction of 88% and a weight of 2 times that of vinyltrimethoxysilane was added and the mixture was stirred and reacted for 6 hours. The mixture was allowed to stand at 20°C for 9 hours. The lower layer of oil was separated by a separatory funnel and dried at 20°C and 5Pa for 9 hours to obtain hyperbranched polysiloxane. The vinyl silicone oil, W-type chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane were mixed uniformly in a mass ratio of 12:25:10:6.5. A dipentadienyl vulcanizing agent with a weight of 0.06 times that of the vinyl silicone oil was added. The mixture was stirred at 65°C and 900 r / min for 25 minutes. The mixture was allowed to stand at room temperature for 22 hours. The mixture was then placed in a mold and vulcanized at 165°C and 490 MPa for 3 hours to obtain a silicone rubber composite material for fire-resistant cables. The remaining steps were the same as those in Example 2.

[0054] Effect example

[0055] Table 1 below shows the performance analysis results of the anti-fracture performance and fire resistance performance of the silicone rubber composite materials for fire-resistant cables of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0056] Table 1

[0057] Tensile Strength Limiting oxygen index Cooling amount Tensile Strength Limiting oxygen index Example 1 13.3MPa 43.5% Comparative Example 3 13.0MPa 38.7% Example 2 13.8MPa 43.6% Comparative Example 4 11.6MPa 40.4% Example 3 13.5MPa 43.3% Comparative Example 5 9.8MPa 39.8% Comparative Example 1 13.4MPa 36.8% Comparative Example 6 11.8MPa 43.2% Comparative Example 2 13.3MPa 39.3%

[0058] From the comparison of the experimental data of Examples 1 to 3 and Comparative Tables 1 to 6 in Table 1, it can be found that the silicone rubber composite material for fire-resistant cables prepared in the present invention has good fracture resistance and fire resistance.

[0059] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is higher than that of Comparative Example 1, which indicates that when potassium carbonate and sodium carbonate are calcined, gas and potassium oxide and sodium oxide can be generated, and the calcined and molten inorganic components can be mixed evenly. At the same time, the generated potassium oxide and sodium oxide can provide free oxygen, which can combine with bismuth to form more [BiO 3 ]tetrahedron and [BiO 6] octahedral structure, resulting in a decrease in the integrity of the inorganic network formed by boron, silicon and oxygen elements, making the obtained low-melting-point inorganic particles easier to melt, and can respond to high temperatures in a timely manner and form a molten state to cover the surface of the cable for fire protection and heat insulation, thereby improving the fire resistance of the silicone rubber composite material for fire-resistant cables; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 2, which shows that multi-stage cooling treatment can avoid uneven mixing of the various components of the low-melting-point inorganic particles obtained by rapidly cooling the glass melt at room temperature, thereby improving the fire resistance of the silicone rubber composite material for fire-resistant cables; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found , the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 3, which indicates that the pre-modification of the low-melting-point inorganic particles can protect the low-melting-point inorganic particles and prevent the loss of the low-melting-point inorganic particles, thereby improving the fire resistance of the silicone rubber composite material for fire-resistant cables; from the comparison of the experimental data of Examples 1, 2, and 3 and Comparative Example 4, it can be found that the tensile strength and limiting oxygen index of Examples 1, 2, and 3 are higher than that of Comparative Example 4, which indicates that methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane are reacted and grafted on the pre-modified inorganic particles to form branched long chains to prepare modified inorganic particles, and the vinyl groups contained in the branched long chains can participate in the subsequent vulcanization, so that the modified inorganic particles are more suitable for fire-resistant cables. The main body of the silicone rubber composite material plays a role of cross-linking and strengthening, thereby improving the fracture strength of the silicone rubber composite material for fire-resistant cables. At high temperature, molten inorganic matter is formed inside the modified inorganic particles, and the branched long chains are disconnected and cross-linked to form free radicals on the outside of the modified inorganic particles. It has good compatibility with the molten inorganic matter and guides the outflow and expansion of the molten inorganic matter, thereby improving the fire resistance of the silicone rubber composite material for fire-resistant cables. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the tensile strength and limiting oxygen index of Examples 1, 2, and 3 are higher than those of Comparative Example 5, which shows that the addition of hyperbranched polysiloxane and the vinyl contained in the hyperbranched polysiloxane can participate in the subsequent vulcanization, and the hyperbranched structure can improve the cross-linking effect. , and the branching gap is easy to fix other components, thereby improving the fracture strength of the silicone rubber composite material for fire-resistant cables. When melted, the hyperbranched polysiloxane has good fluidity and compatibility with inorganic substances, avoiding the dripping of molten inorganic substances, and adhering to the cable conductor to avoid bare leakage of the conductor, thereby improving the fire resistance of the silicone rubber composite material for fire-resistant cables; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the tensile strength of Examples 1, 2, and 3 with Comparative Example 6 is high, which shows that the two-stage vulcanization treatment is carried out to volatilize the volatile small molecules and small molecule free radicals in the components, avoiding the small molecules and small molecule free radicals causing a decrease in the degree of crosslinking, thereby improving the fracture strength of the silicone rubber composite material for fire-resistant cables.

[0060] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a silicone rubber composite material for a fire-resistant cable, characterized in that: The preparation method of the silicone rubber composite material for fire-resistant cable comprises the following preparation steps: (1) Sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are uniformly mixed in a mass ratio of 1:1:4:16:16, calcined at 1000°C for 60 minutes, and then subjected to a multi-stage cooling treatment, cooling at 400°C for 3 hours, cooling at 100°C for 2 hours, and cooling at 10°C for 60 minutes, and then ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles; (2) Low-melting-point inorganic particles and 30% by mass of ammonia water, anhydrous ethanol and pure water were mixed in a ratio of 1:2:4:2, and then 1 times the mass of low-melting-point inorganic particles of tetraethyl orthosilicate was added, and the mixture was stirred at 20°C and 500 r / min for 3 hours, and then filtered, and washed with deionized water and anhydrous ethanol three times each, and then immersed in a 5% by mass sodium hydroxide solution, and ultrasonically reacted at 50°C and 30kHz for 24 hours, and then filtered, and washed with pure water and anhydrous ethanol three times each, and dried at -10°C and 5Pa for 8 hours to obtain a prepreg. Modifying inorganic particles: methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol are uniformly mixed in a mass ratio of 1:3:2:8 in a nitrogen atmosphere, and then the pH is adjusted to 2.9 with 3% hydrochloric acid, and stirred at 30°C and 500r / min for 50min, and then pre-modified inorganic particles with a mass of 1 times that of methyltrimethoxysilane are added, and the mixture is stirred at 70°C and 500r / min for 18h, filtered and washed with anhydrous ethanol for 3 times, and dried at 60°C for 6h to obtain modified inorganic particles; (3) In a nitrogen atmosphere, methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed in a mass ratio of 1:3:2:8, and then the pH was adjusted to 2.9 with 3% hydrochloric acid. The mixture was stirred at 30°C and 500 r / min for 40 min. Then, an organic silicon mixed solution prepared by mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:3:2 with a mass ratio of 1.4 times that of vinyltrimethoxysilane was added. The mixture was stirred at 50°C and 500 r / min for 3 h. The mixture was heated to 70°C and stirred for 9 h. Then, 85% hexamethyldisilazane with a mass ratio of 1.9 times that of vinyltrimethoxysilane was added. The oxane aqueous solution was stirred and reacted for 7 hours, and the mixture was allowed to stand at 10°C for 10 hours. The lower layer of oil was separated by a separatory funnel and dried at 10°C and 1Pa for 10 hours to obtain hyperbranched polysiloxane; vinyl silicone oil, W-type chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane were evenly mixed in a mass ratio of 10:20:8:5, and a dipentadienyl vulcanizing agent with a mass of 0.05 times that of the vinyl silicone oil was added, and the mixture was stirred at 60°C and 800r / min for 30 minutes, and allowed to stand at room temperature for 24 hours, and then placed in a mold for one-stage vulcanization, and vulcanized at 160°C and 480MPa for 30 minutes, and then vulcanized in a vacuum drying oven for two stages, and vulcanized at 170°C and 300Pa for 3 hours to obtain a silicone rubber composite material for fire-resistant cables.

2. A method for preparing a silicone rubber composite material for a fire-resistant cable, characterized in that: The preparation method of the silicone rubber composite material for fire-resistant cables comprises the following preparation steps: (1) Sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are uniformly mixed in a mass ratio of 1:1:5:19:18, calcined at 1100°C for 55 minutes, and then subjected to a multi-stage cooling treatment, cooling at 450°C for 2.5 hours, cooling at 120°C for 1.5 hours, and cooling at 20°C for 55 minutes, and then ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles; (2) Low-melting-point inorganic particles and 28% by mass of ammonia water, anhydrous ethanol and pure water were mixed in a ratio of 1:2.5:4.5:2, and then 1.1 times the mass of low-melting-point inorganic particles of tetraethyl orthosilicate was added. The mixture was stirred at 25°C and 650 r / min for 2.5 h, and then filtered. The mixture was washed with deionized water and anhydrous ethanol four times each, and then immersed in a 6% by mass sodium hydroxide solution. The mixture was ultrasonically reacted at 55°C and 35kHz for 23 h, and then filtered. The mixture was washed with pure water and anhydrous ethanol four times each, and then dried at -5°C and 8Pa for 7 h to prepare a To obtain pre-modified inorganic particles, methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed uniformly in a mass ratio of 1:3.5:2:9 in a nitrogen atmosphere, and the pH was adjusted to 3 with 4% hydrochloric acid, and stirred at 35°C and 650r / min for 45min, and then 1.5 times the mass of methyltrimethoxysilane pre-modified inorganic particles were added, and the mixture was stirred at 74°C and 650r / min for 16h, filtered and washed with anhydrous ethanol for 4 times, and dried at 65°C for 5h to obtain modified inorganic particles; (3) In a nitrogen atmosphere, methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed in a mass ratio of 1:3.5:2:9, and then the pH was adjusted to 3 with 4% hydrochloric acid. The mixture was stirred at 35°C and 600 r / min for 45 min. Then, an organic silicon mixed solution prepared by mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:3.5:2.5 with a mass ratio of 1.5 times that of vinyltrimethoxysilane was added. The mixture was stirred at 55°C and 650 r / min for 2.5 h. The mixture was heated to 74°C and stirred for 8 h. Then, 88% hexamethyldisilazane with a mass ratio of 2 times that of vinyltrimethoxysilane was added. The oxane aqueous solution was stirred and reacted for 6 hours, and then allowed to stand at 20°C for 9 hours. The lower layer of oil was separated by a separatory funnel and dried at 20°C and 5Pa for 9 hours to obtain hyperbranched polysiloxane; vinyl silicone oil, W-type chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane were evenly mixed in a mass ratio of 12:25:10:6.5, and a dipentadienyl vulcanizing agent with a mass of 0.06 times that of the vinyl silicone oil was added, and stirred at 65°C and 900r / min for 25 minutes, and allowed to stand at room temperature for 22 hours, and then placed in a mold for one-stage vulcanization, and vulcanized at 165°C and 490MPa for 25 minutes, and then vulcanized in a vacuum drying oven for two stages, and vulcanized at 175°C and 400Pa for 2.5 hours to obtain a silicone rubber composite material for fire-resistant cables.

3. A method for preparing a silicone rubber composite material for a fire-resistant cable, characterized in that: The preparation method of the silicone rubber composite material for fire-resistant cable comprises the following preparation steps: (1) Sodium carbonate, potassium carbonate, boric acid, silicon dioxide and bismuth trioxide are uniformly mixed in a mass ratio of 11:1:6:22:20, calcined at 1200°C for 50 minutes, and then subjected to a multi-stage cooling treatment, cooling at 500°C for 2 hours, cooling at 150°C for 1 hour, and cooling at 10°C for 50 minutes, and then ground in a pulverizer to a particle size of less than 0.5 mm to obtain low-melting-point inorganic particles; (2) Low-melting-point inorganic particles and 25% by mass of ammonia water, anhydrous ethanol and pure water were mixed in a ratio of 1:3:5:2, and then 1.2 times the mass of low-melting-point inorganic particles of tetraethyl orthosilicate was added, and the mixture was stirred at 30°C and 800 r / min for 3 hours, and then filtered, and washed with deionized water and anhydrous ethanol for 5 times respectively, and then immersed in 8% by mass sodium hydroxide solution, and ultrasonically reacted at 60°C and 40kHz for 22 hours, and then filtered, and washed with pure water and anhydrous ethanol for 5 times respectively, and dried at -1°C and 10Pa for 8 hours to obtain a prepreg. Modifying inorganic particles: methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol are uniformly mixed in a mass ratio of 1:4:2:10 in a nitrogen atmosphere, and then the pH is adjusted to 3.1 with 5% by mass hydrochloric acid, and stirred at 40°C and 800 r / min for 40 minutes, and then pre-modified inorganic particles twice the mass of methyltrimethoxysilane are added, and the reaction is stirred at 78°C and 800 r / min for 18 hours, filtered and washed with anhydrous ethanol for 5 times, and dried at 70°C for 4 hours to obtain modified inorganic particles; (3) In a nitrogen atmosphere, methyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane and ethanol were mixed in a mass ratio of 1:4:2:10, and then the pH was adjusted to 3.1 with 5% hydrochloric acid. The mixture was stirred at 40°C and 800 r / min for 40 min. Then, an organic silicon mixed solution prepared by mixing methyltrimethoxysilane, diphenyldimethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:4:3 with 1.6 times the mass of vinyltrimethoxysilane was added. The mixture was stirred at 60°C and 800 r / min for 2 h. The mixture was heated to 78°C and stirred for 7 h. Then, 85% hexamethyldisilazane with a mass fraction of 2.1 times the mass of vinyltrimethoxysilane was added. The oxane aqueous solution was stirred and reacted for 5 hours, and then allowed to stand at 30°C for 8 hours. The lower layer of oil was separated by a separatory funnel and dried at 30°C and 10Pa for 8 hours to obtain hyperbranched polysiloxane; vinyl silicone oil, W-type chloroprene rubber, modified inorganic particles and hyperbranched polysiloxane were evenly mixed in a mass ratio of 15:30:12:8, and a dipentadienyl vulcanizing agent with a mass of 0.08 times that of the vinyl silicone oil was added, and the mixture was stirred at 70°C and 1000r / min for 30 minutes, and allowed to stand at room temperature for 20 hours, and then placed in a mold for one-stage vulcanization, and vulcanized at 170°C and 500MPa for 30 minutes, and then vulcanized in a vacuum drying oven for two stages, and vulcanized at 180°C and 500Pa for 2 hours to obtain a silicone rubber composite material for fire-resistant cables.

Citation Information

Patent Citations

  • Preparation method of leadless glass powder for electronic slurry

    CN101215091A

  • A fireproof fire-resistant silicone rubber cable material

    CN105968818A

  • Fireproof flame-retardant plastic optical cable and preparation method thereof

    CN112904510A